Peran Notaris Dalam Hal Perolehan Pengakuan Badan Hukum Perseroan Terbatas Melalui Sistem Administrasi Badan Hukum (SABH) - Argyanti Nariswari, Anak Agung Istri Intan; Cakabawa Landra, Putu Tuni (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p14, 2021)
In the era of globalization, many entrepreneurs  developing their businesses by creating companies. But in the case, only Limited Liability companies can obtain a legal status. Limited Liability Company is regulated in UU Nomor 40 Tahun 2007. The issue that will be discussed is how the role of the notary public in obtaining the status of a legal entity PT which was approved by SABH and the problems that have been faced by a notary in terms of obtaining the status of the legal entity. This research used empirical research, by using fact approach and law approach. With that research method, it was found that the role of the notary in obtaining the status of a legal entity PT in SABH access is, the Notary log in or enters into the SABH system through a SABH account owned by a Notary; Access a copy of the limited company deed by entering the company data requested by the system to the SABH table; Entering the business fields that have been included in the current deed, the business fields must be the same and consistent with the 2017 Indonesian Business Field Standard Classification (KBLI), this is related to the next stage in the management of company business licenses; After everything is already inputted will publish  a Decree of the Minister of Law and Human Rights of the Republic of Indonesia regarding the legalization of the of a Limited Liability Company.